Analisis Praktik Zakat Sebagai Pengurang Penghasilan Kena Pajak (Studi Kasus BAZNAS Kabupaten Deli Serdang) - Aulia, Jihan Luthfi; Juliati Nasution, Yenni Samri; Nurwani, Nurwani (Ekonomi Bisnis Manajemen dan Akuntansi (EBMA), 2022)
Tax and zakat are similar because both function as a collection tool. As a solution so that obligatory zakat is not exposed to the double burden and both obligations are carried out by Muslims without burdening them, the government issued a regulation, namely law No. 23 of 2011 on zakat management. This study aims to answer how the application of zakat as a deduction of taxable income in BAZNAS Deli Serdang, what are the inhibiting factors and efforts made in the application of zakat as a deduction of taxable income. Researchers used qualitative research with descriptive approach. Types and sources of data in this study consisted of primary and secondary data. Primary Data comes from interviews, while secondary data comes from books, journals, laws, evidence of Zakat deposits, and others. Furthermore, the data collection methods used are observation, interviews, documentation. In analyzing the data through four stages, namely: data collection, data reduction, data presentation, and conclusion. The results showed that the application of zakat as a deduction for taxable income in BAZNAS Deli Serdang has not been fully implemented, due to several obstacles, namely the lack of awareness of Muslims to pay zakat in BAZNAS, the lack of public knowledge about the function and usefulness of zakat and lack of trust in BAZNAS, has not fully provided evidence of Zakat deposits to muzakki, the absence of an appeal from the central BAZNAS regarding the regulation to BAZNAS Deli Serdang. The settlement efforts that will be carried out by BAZNAS Deli Serdang regency are publishing a bulletin/brochure on zakat as a deduction for taxable income, conducting socialization on zakat management, and providing proof of Zakat deposit to each muzaki.